Quantification of voltage profiles intermittency for small-scale solar photovoltaic system under different loading conditions - Mohd Azman, Mohd Arif; Gan, Chin Kim; Baharin, Kyairul Azmi (International Journal of Renewable Energy Research, 2020)
The recent rapid uptake of solar photovoltaic system in Malaysia has introduced new challenges to the operation of the power grid, particularly on the voltage profile of distribution networks. An intermittent nature of the voltage fluctuation that caused by solar output remain as important topic as how these rapid voltage changes will affect the operation of the network. Hence, this paper presents a quantification of voltage profiles intermittency for small-scale solar photovoltaic system under different loading conditions. Actual field measurements have been performed for both high and low loading conditions. Mainly two parameters have been analysed for this work, namely voltage profile and solar power output. An intermittency quantity of voltage profile during solar generation for day time is higher than night time, which indicates high intermittent in solar irradiance causing rapid fluctuation in solar generation. Furthermore, increased voltage magnitude was observed during the low load condition. The high voltage intermittency caused by rapid fluctuation of solar output and voltage rise during low load giving a negative effect on distribution network. It is expected that grid-connected battery energy storage system could serve as the potential solution to alleviate both solar intermittency and voltage raise issues.